Evaluating thermal comfort indices for outdoor spaces on a university campus - Jing, Wenqiang; Qin, Zeming; Mu, Teng; Ge, Zhemin; Dong, Yuting (Scientific reports, 2024)
This study evaluates the applicability of three thermal comfort indices—Physiologically Equivalent Temperature (PET), Standard Effective Temperature (SET), and Universal Thermal Climate Index (UTCI)—in various outdoor environments on the campus of Xi’an University, China. Meteorological data were collected on sunny days using a portable weather station at a height of 1.5 m, and subjective questionnaires were administered to 25 healthy university students over three months to gather Thermal Sensation Votes (TSV) and Thermal Comfort Votes (TCV). The study was conducted at four distinct outdoor locations: a lakeside area (Location 1), a shaded path (Location 2), a sports field (Location 3), and a plaza (Location 4). PET, SET, and UTCI values were calculated from the collected data using Rayman software. The analysis revealed significant differences in thermal comfort across the four locations, with the highest proportion of subjects feeling hot at the sports field (54.4%) and the highest proportion feeling cold at the lakeside (39%). The shaded path had the highest proportion of subjects feeling comfortable (79.4%), while the lakeside had the lowest (60.1%). The results indicated that SET underestimated thermal sensation at Locations 1, 3, and 4, necessitating calibration. PET was suitable for Locations 2, 3, and 4 but failed to reflect the thermal sensation at Location 1 due to prolonged sun exposure. In contrast, UTCI demonstrated applicability across all locations. To enhance accuracy, revised indices SET’ and PET’ were formulated using the mean-median method, providing more precise thermal comfort assessments. These findings underscore the limitations of SET and PET under specific conditions and highlight the robustness of UTCI, offering valuable insights for urban planning and design aimed at improving outdoor thermal comfort and well-being.